Model Matematika terhadap Dinamika Kecanduan Judi Online pada Masyarakat Desa Tanjung Putus - Fadila Inka Syahfitri; Erika Handayani Br. Siahaan; Fani Indriyani Ningsih; Apriyani Sitompul (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study develops a mathematical model to analyze the dynamics of online gambling addiction among the Tanjung Putus Village community using the SEIR (Susceptible-Exposed-Infectious-Recovered) model approach. This model aims to understand how the spread of online gambling addiction develops within a community and identify factors that affect the transition of individuals from one status to another, from susceptible (Susceptible), exposed (Exposed), infected (Infectious), to recovered (Recovered). The results show that although the number of recovered individuals continues to increase, the recovery rate (R) remains slow due to the low recovery rate ( ). This indicates that without more effective interventions, infected individuals will remain trapped in addiction for a long time.